2020
DOI: 10.1002/hep.31167
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Deficiency of Augmenter of Liver Regeneration Predisposes to Nonalcoholic Steatohepatitis and Fibrosis

Abstract: Background and Aims The augmenter of liver regeneration (ALR) protein is critical for lipid homeostasis and mitochondrial function. We investigated high‐fat/high‐carbohydrate (HF/HC) diet–induced nonalcoholic fatty liver disease (NAFLD) in wild‐type (WT), hepatocyte‐specific ALR‐knockout (ALR‐H‐KO), and ALR‐heterozygous (ALR‐H‐HET) mice. ALR was measured in serum of human nonalcoholic steatohepatitis (NASH) and NASH‐induced cirrhosis (serum and liver). Approach and Results HF/HC feeding decreased ALR expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 43 publications
(93 reference statements)
1
47
0
Order By: Relevance
“…In earlier publications, using an overexpression approach ("gain-of-function") of the mainly mitochondrial 23-kDa ALR, a reduction in hepatic fibrosis and ischemia reperfusion injury (IRI) in steatotic livers was shown. (2) Expression of cytosolic 15-kDa ALR reduced severity of liver injury in a methionine-choline-deficient NASH mouse model. (2) Furthermore, it was shown that cytosolic 15-kDa ALR, different from exogenously applied 15-kDa ALR, diminished triacylglycerol levels and lipoapotosis in vitro by attenuating endoplasmatic stress, increasing lipolytic and decreasing lipogenic gene expression.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In earlier publications, using an overexpression approach ("gain-of-function") of the mainly mitochondrial 23-kDa ALR, a reduction in hepatic fibrosis and ischemia reperfusion injury (IRI) in steatotic livers was shown. (2) Expression of cytosolic 15-kDa ALR reduced severity of liver injury in a methionine-choline-deficient NASH mouse model. (2) Furthermore, it was shown that cytosolic 15-kDa ALR, different from exogenously applied 15-kDa ALR, diminished triacylglycerol levels and lipoapotosis in vitro by attenuating endoplasmatic stress, increasing lipolytic and decreasing lipogenic gene expression.…”
mentioning
confidence: 99%
“…(2) Expression of cytosolic 15-kDa ALR reduced severity of liver injury in a methionine-choline-deficient NASH mouse model. (2) Furthermore, it was shown that cytosolic 15-kDa ALR, different from exogenously applied 15-kDa ALR, diminished triacylglycerol levels and lipoapotosis in vitro by attenuating endoplasmatic stress, increasing lipolytic and decreasing lipogenic gene expression. (3) Additionally, treatment with exogenous ALR reduced hepatic IRI in mice by reducing neutrophil infiltration through less hepatocytic chemokine expression.…”
mentioning
confidence: 99%
See 3 more Smart Citations